Data, open research data and intellectual property - Barreto-Granada, Piedad Lucía; Guzmán Díaz, José Cruz; Martínez Martínez, Lorena (DIXI, 2025)
The objective of this article is to analyze the distinguishing elements among the concepts of data from a human perspective, computational data, open data, and open research data, in order to provide insight into their value in fulfilling two key interests: a general one, related to open science, and a particular one, linked to their potential as a source of wealth in commercial contexts based on intellectual property. To this end, a literature review was conducted using academic databases and the websites of multilateral organizations. The findings highlight a challenge for all countries, as political and economic power must align with the protection of human beings by ensuring ethical principles, appropriate regulations, and safeguards for both present and future citizens.